2016
DOI: 10.5628/rpcd.16.03.44
|View full text |Cite
|
Sign up to set email alerts
|

Interação e network de sequências ofensivas coletivas: Análise de uma seleção de Sub-20 no Campeonato do Mundo de Futebol

Abstract: Este estudo teve como objetivo analisar a interação e network de sequências ofensivas coletivas que resultaram em finalização de uma Seleção de Futebol de Sub-20. A amostra consistiu na análise de 76 ações ofensivas que foram transformadas em golo. Foi realizada uma análise quantitativa e qualitativa das ações de jogo através do software VideObserver ®. As networks de interação entre jogadores foram obtidas através do mesmo programa. As métricas de centralidade foram calculadas através do software Social Netwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 8 publications
4
5
0
Order By: Relevance
“…The passing sequences results are in accordance with the studies of Reep and Benjamin (1968), Hughes and Franks (2005) and Alves et al (2016) where most of the actions and goals scored occurred in shorter passing sequences. The data are also in agreement with McLean, Salmon, Gorman, Naughton and Solomon (2017a), who compared the Euro 2016 and American Cup 2016 and found that most of the goals scored occurred from shorter passing sequences.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…The passing sequences results are in accordance with the studies of Reep and Benjamin (1968), Hughes and Franks (2005) and Alves et al (2016) where most of the actions and goals scored occurred in shorter passing sequences. The data are also in agreement with McLean, Salmon, Gorman, Naughton and Solomon (2017a), who compared the Euro 2016 and American Cup 2016 and found that most of the goals scored occurred from shorter passing sequences.…”
Section: Resultssupporting
confidence: 88%
“…On the other hand, the player who received the most interactions was player number 7 (forward), with a total of 65 interactions received. Finally, at the level of interventions (sum of interactions made and received (Gama et al, 2014;Alves et al, 2016), the players with the highest values were player number 7 (forward), with a total of 103 interventions, followed by player number 10 (midfielder), with a total of 90 interventions, and finally player number 17 (number), with a total of 89 interventions. Caption: The team's direction of attack is displayed through the black arrow displayed along the playing field charts.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations